Age‐related changes of skeletal muscle metabolic response to contraction are also sex‐dependent - Campbell, Matthew D.; Djukovic, Danijel; Raftery, Daniel; Marcinek, David J. (The Journal of physiology, 2025)
Mitochondria adapt to increased energy demands during muscle contraction by acutely altering metabolite fluxes and substrate oxidation. With age, an impaired mitochondrial metabolic response may contribute to reduced exercise tolerance and decreased skeletal muscle mass, specific force, increased overall fatty depositions in the skeletal muscle, frailty and depressed energy maintenance. We hypothesized that elevated energy stress in mitochondria with age alters the capacity of mitochondria to utilize different substrates following muscle contraction. To test this hypothesis, we used in vivo electrical stimulation to simulate high‐intensity intervals (HII) or low intensity steady‐state (LISS) exercise in young (5–7 months) and aged (27–29 months) male and female mice to characterize effects of age and sex on mitochondrial substrate utilization in skeletal muscle following contraction. Mitochondrial respiration using glutamate decreased in aged males following HII and glutamate oxidation was inhibited following HII in both the contracted and non‐stimulated muscle of aged female muscle. Analyses of the muscle metabolome of female mice indicated that changes in metabolic pathways induced by HII and LISS contractions in young muscle are absent in aged muscle. To test improved mitochondrial function on substrate utilization following HII, we treated aged females with elamipretide (ELAM), a mitochondrially‐targeted peptide shown to improve mitochondrial bioenergetics and restore redox status in aged muscle. ELAM removed inhibition of glutamate oxidation and showed increased metabolic pathway changes following HII, suggesting rescuing redox status and improving bioenergetic function in mitochondria from aged muscle increases glutamate utilization and enhances the metabolic response to muscle contraction in aged muscle. Key points Acute local contraction of gastrocnemius can systemically alter mitochondrial respiration in non‐stimulated muscle. Age‐related changes in mitochondrial respiration using glutamate or palmitoyl carnitine following contraction are sex‐dependent. Respiration using glutamate after high‐intensity contraction is inhibited in aged female muscle. Metabolite level and pathway changes following muscle contraction decrease with age in female mice. Treatment with the mitochondrially‐targeted peptide elamipretide can partially rescue metabolite response to muscle contraction. figure legend Mitochondria respond to metabolic demand of exercise by upregulating metabolic pathways to generate ATP through the utilization of specific substrates. In aged tissue, the mitochondrial substrate utilization response to exercise is reduced or inhibited, causing increased energy stress.